Reach out and give - Meiners, Cheri J., 1957- (Minneapolis, MN : Free Spirit Pub. Inc., 2006)
Simple words and illustrations encourage children to do their part to make the world a better place, focusing on the concept of gratitude.
2.0
K-3
K-3
Keywords: Generosity -- Juvenile literature; Gratitude -- Juvenile literature; Generosity; Gratitude; Generosity; Gratitude